Engineering economic analysis for feed gas cooler (Cold box): A case of a gas processing complex in Malaysia - Ghazali, Z. (EDP Sciences, 2014)
This study examine the economic feasibility of a proposal to replace an existing Feed Gas Cooler (Cold Box) with a new unit in a gas processing complex in Malaysia. Economic justification is essential to make the decision on the feasibility of this undertaking because of the high capital investment. The mathematical model presented in the paper includes net present worth, payback period, rate of return, investment balance analysis, and sensitivity analysis. Critical analyses on four factors of the estimates were done to assess their influence on the overall economic justification of the proposal. The results indicate an acceptable return on investment. However, the proposal is susceptible to the variation in demand of the Feed Gas Load. Â© 2014 Owned by the authors, published by EDP Sciences.